Comparative investigation of the growth-poverty-inequality trilemma in Sub-Saharan Africa and Latin American and Caribbean Countries. Issue 12 (December 2020) - Adeleye, Bosede Ngozi; Gershon, Obindah; Ogundipe, Adeyemi; Owolabi, Oluwarotimi; Ogunrinola, Ifeoluwa; Adediran, Oluwasogo
Abstract: To " end poverty in all its forms everywhere " and " reduce inequality within and among countries ", this study aligns with the 2030 Sustainable Development Goals 1 and 10. It uniquely contributes to the growth-poverty-inequality discourse by using per capita consumption expenditure growth (poverty), Gini index (inequality) and GDP growth (economic growth). It is a comparative analysis of 58 Sub-Saharan Africa (SSA) and Latin American (LAC) countries (from 2000 to 2015) to determine whether economic growth reduces the incidence of poverty and if its interaction with income inequality enhances or alters its impact on poverty. Consistent findings from a multi-analytical approach using pooled ordinary least squares, fixed effects and system GMM reveal that: (1) economic growth exhibit poverty-reduction properties; (2) the growth rate of inequality intensifies poverty, (3) inequality aggravates the impact of growth on poverty, and (4) the growth-poverty-inequality trilemma differs across income groups and regional samples. Furthermore, this study submits that the interaction of income inequality dampens the positive impact of economic growth on the incidence of poverty and supports the argument that the extent of inequality lessens the effect of inclusiveness. Hence, income inequality is a crucial determinant of poverty. Policy implications are discussed. Abstract : Economic Growth; Poverty; Inequality; Sub-Saharan Africa; Latin America and the Caribbean; Inequality; Poverty; Economic Development; Economic Growth; Macroeconomics